Evaluation of the soil–pile interface properties in the lateral direction for seismic analysis in sand. Issue 140 (January 2021) - Tran, Nghiem Xuan; Bong, Taeho; Yoo, Byeong-Soo; Kim, Sung-Ryul
Abstract: This study aimed to numerically evaluate the strength parameter of the soil–pile interface in the lateral direction. A 3D numerical model of a single pile in sandy soil was built to analyse the interface strength parameter, which was defined as the ratio of the lateral force mobilised on the interface to the confining stress multiplied by the pile perimeter. Results showed that the interface strength parameter increased with the embedment depth ratio and converged to a constant value at a depth of four times the pile diameter. This relationship can be expressed using a bilinear formula that can be adopted to define the strength of springs connecting soil and pile elements in the lateral direction. The applicability of the proposed strength parameter to seismic analysis was validated by performing 3D numerical simulations of centrifuge tests. The simulation targeted single and group piles installed in a level ground of dry silica sand. The simulation results agreed well with the measured data, indicating the reasonable applicability of the proposed strength parameter of the soil–pile interface in the lateral direction. Highlights: Shallow and deep failure mechanisms at lateral soil–pile interface were evaluated by performing 3D numerical simulation. Relationship between normal and confining stresses at lateral soil–pile interface was obtained. A bilinear formula was proposed to define strength parameter of lateral soil–pile interface in numerical modelling. Proposed strength parameter was applicable to seismic analysis of pile-supported structures in dry sand.